The Economic Burden of Schizophrenia in the United States in 2019. (April 2022) - Kadakia, Aditi; Fan, Angela; Marden, Jessica; Dembek, Carole; Catillon, Maryaline; Anderson, Annika; Williams, Rhys
Abstract: Background: Schizophrenia is associated with health, social, and financial burdens for patients, caregivers, and society. Major systemic changes, reforms, and technological advances have happened in the USA since the prior estimate of the societal cost of schizophrenia, $155.7B in 2013. This study analyzes the most recent data and literature to update this estimate. Methods: Direct and indirect costs associated with schizophrenia in the US in 2019 were estimated using a prevalence-based approach (ICD-10 codes: F20, F25). Direct healthcare costs were assessed retrospectively using a matched cohort design in the IBM Watson Health MarketScan Commercial, Medicare, and Medicaid databases from October 1, 2015, through December 31, 2019. Patients were matched to controls on demographics, insurance type, and index year. Direct nonhealthcare costs were estimated using published literature and government data. Indirect costs were estimated using a human capital approach and the value of quality-adjusted life years lost. Cost offsets were applied to account for basic living costs avoided. Excess costs, comparing costs for individuals with and without schizophrenia, were reported in 2019 USD. Results: The estimated excess economic burden of schizophrenia in the US in 2019 was $330.6B, including $62.3B in direct healthcare costs (19%), $19.7B in direct nonhealthcare costs (5%), and $251.9B in excess indirect costs (76%). The largest drivers of indirect costs were caregiving ($112.3B), premature mortality ($77.9B), and unemployment ($54.2B). Conclusions: The estimated societal burden of schizophrenia in the USA in 2019 was $330.6B, which represented a 93.5% increase from 2013 to 2019, after accounting for inflation. This study underscores the increasing and apparent burden of schizophrenia not only on the patient, but also on caregivers and society. Funding: Sunovion Pharmaceuticals